THE INFLUENCE FACTORS OF TEACHER PERFORMANCE - Suryadi Suryadi; Agustin HP; Hari Sukarno (MBA - Journal of Management and Business Aplication, 2018)
The purpose of the research was to analyze and examine the influence of the principal managerial competence, motivation and work discipline on teacher performance, both partially and simultaneously. This research was explanatory survey research. The population of the research was the whole teacher of SMA Negeri 1 Cluring, Banyuwangi totaling 39 teachers. The sample used was 31 teachers, chosen by purposive sampling technique. The preparation of the instrument was made in the form of a questionnaire, with a scale of 1-5 answers, consisting of 37 items. The instrument items used to collect data are those that meet the requirements of construct analysis and have valid status. Its reliability is calculated by the Cronbach's Alpha technique. Data collection methods used in this research were observation, interview, questionnaire, and through documentation. Data analysis used multiple linear regression. Based on the results of research and analysis of the data, it showed that the principal managerial competence, motivation and work discipline influenced to the teacher performance significantly both partially and simultaneously. Test results partially were evidenced by the significant value to the variable of the managerial competence that was 0.048, then the significant value of motivation variable was 0.014 and for work discipline was 0.016. So the amount of significance value was smaller than 0.05. The results of the test simultaneously were demonstrated by the value of the principal managerial competence, motivation and work discipline to the teacher performance that was 0.000. Therefore, the significance value was smaller than 0.05. Keywords: The Principal Managerial Competence, Motivation, Work Discipline, Teacher Performance